Evaluating the toxicity of the antiPCSK9 vaccine in the animal model. (3rd October 2022) - Momtazi-Borojeni, A A; Ataei, S; Sarborji, M R; Hatamipour, M R; Tabatabaei, S A; Banach, M; Sahebkar, A
Abstract: Background: Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibition is a novel cholesterol-lowering treatment for decreasing the risk of atherosclerosis. We have previously shown that active immunization using the antiPCSK9 vaccine could decrease hypercholesterolemia and impede the development of atherosclerotic lesions in the experimental model of atherosclerosis. Purpose: Here, we intended to evaluate the toxicity of the vaccine in healthy mice. Methods: Forty male and female mice were divided into 4 experimental groups, including vaccine female (10 mice) and male (10 mice) groups receiving the antiPCSK9 vaccine as well as corresponding control female (10 mice) and male (10 mice) groups receiving the phosphate buffer. Vaccination was planned based on 4 subcutaneous injections of the vaccine formulation (10 μg/mouse) in bi-weekly intervals. The toxicity study was performed by the sub-acute protocol, 28 days after the last vaccine injection. To this end, the plasma levels of lipid indexes, urea, creatinine, AST, ALT, ALP, and fasting plasma glucose (FPG), as well as the CBC test were measured using commercial kits. To evaluate histopathological alterations, various tissues including the heart, liver, kidneys, spleen, and brain were studied using hematoxylin & eosin (H&E) staining by an expert pathologist. The severity of damage to the tissue was considered based on the standard classification; grade 1 as light damage, grade 2 as moderate damage, grade 3 as the bit-intense damage, and grade 4 as the intense damage. Results: The results showed the non-significant changes of total cholesterol, triglyceride, HDL-C, FBS, creatinine, urea, AST, ALP, ALT, and PAB in the vaccinated mice when compared with control mice. However, plasma levels of LDL-C were significantly decreased in vaccinated male (by16.93±2.5 mg/dL, p=0.001) and female mice (by 22±2.7 mg/dL, p=0.001) when compared with corresponding control mice. CBS test indicated that there were no significant changes in the levels of WBC, RBC, HGB, HCT, MCH, MCHC, PLT, LYM, NEUT, PDW, and MPV in the vaccinated mice when compared with control mice. However, the levels of MCV, RDW-SD, and P-LCR were significantly decreased by (4.6±1.2 fL, p=0.02), (4±0.6 fL, p=0.001), and (0.13±0.01%, p=0.001), respectively, in vaccinated male mice when compared with control male mice. Evaluating histopathological alterations in various tissues indicated no significant adverse effects in vaccinated mice when compared to control mice. Conclusions: The findings of the present study indicate that the antiPCSK9 is safe and exerts no adverse effects on the function of different organs and blood levels of the cellular and biochemical biomarkers in healthy mice. Funding Acknowledgement: Type of funding sources: None.